2023
DOI: 10.1029/2023je007793
|View full text |Cite
|
Sign up to set email alerts
|

Focal Mechanism Determination of Event S1222a and Implications for Tectonics Near the Dichotomy Boundary in Southern Elysium Planitia, Mars

R. Maguire,
V. Lekić,
D. Kim
et al.

Abstract: On 4 May 2022 the InSight seismometer SEIS‐VBB recorded the largest marsquake ever observed, S1222a, with an initial magnitude estimate of 4.6. Understanding the depth and source properties of this event has important implications for the nature of tectonic activity on Mars. Located ∼37° to the southeast of InSight, S1222a is one of the few non‐impact marsquakes that exhibits prominent surface waves. We use waveform modeling of body waves (P and S) and surface waves (Rayleigh and Love) to constrain the focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…The tectonic setting within the epicentral ellipse is very different to that of the Cerberus Fosse region where the strongest other tectonic marsquakes have occurred (Kawamura et al, 2022;Stähler et al, 2022). Initial results suggest a dip-slip fault in the mid-crust (Maguire et al, 2023), consistent with an origin between 18 and 28 km depth. Further analysis is ongoing.…”
Section: Discussionmentioning
confidence: 83%
“…The tectonic setting within the epicentral ellipse is very different to that of the Cerberus Fosse region where the strongest other tectonic marsquakes have occurred (Kawamura et al, 2022;Stähler et al, 2022). Initial results suggest a dip-slip fault in the mid-crust (Maguire et al, 2023), consistent with an origin between 18 and 28 km depth. Further analysis is ongoing.…”
Section: Discussionmentioning
confidence: 83%
“…Although we also performed calculations in the 1D layered velocity model mentioned in Earth and Space Science 10.1029/2023EA003272 several frequency ranges, the solutions for the interval 0.028-0.072 Hz were chosen to illustrate outcome from the full-waveform MT inversion. This range was used in Maguire et al (2023).…”
Section: Results-low-frequency Full-waveform Moment Tensor Inversion ...mentioning
confidence: 99%
“…Recently, Maguire et al (2023) used waveform fitting of body waves and surface waves to estimate the moment tensor solution of S1222a and found that either an E-W to SE-NW striking thrust fault or normal fault can explain the data. For the same structural model and frequency range used in this study and in Maguire et al (2023) for low-frequency MT inversion waveform (within the estimated error) similar solutions were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations